Challenges in managing ossifying fibroma of the maxilla: A case report - Prisca Anindhita; Hery Susilo; Wilma Agustina; Yudi Siswanto (Romanian Medical Journal)
Ossifying fibroma (OF) is a rare benign bone tumor that tends to grow aggressively, particularly in craniofacial bones such as the upper and lower jaw. The diagnosis of OF is often challenging, due to its rare nature and ability to invade adjacent anatomical structures. We present a case of OF in a 35-year-old woman with recurrent complaints of a lump on the right side of the face. Imaging evaluation showed widespread lesions in the right maxilla. Multidisciplinary discussion was required to determine the best approach in the management of this case, focusing on complete excision of the tumor while preserving function and aesthetics. In the context of recurrent or extensive disease, reconstructive techniques using local or distant flaps can be important to restore postoperative structure and function. Close postoperative surveillance is required to monitor for recurrence and facilitate timely intervention. With a multidisciplinary approach and appropriate management strategies, challenging OF cases can be effectively managed, although more research is needed to improve understanding and outcomes in this condition.